SUBSURFACE MODELLING OF BANDA API VOLCANO AREA BASED ON GRAVITY DATA - Ardana, Fauzan
Indonesia is located in the southern part of the Eurasian Plate which is directly opposite the Indo-Australian Plate and the Pacific Plate where energy accumulation occurs at the meeting of these plates. This causes Indonesia to have 127 active volcanoes so that volcanic research is important to do. Mount Banda Api is type A and has many eruption records since 1600 which became the object of research in this study. The purpose of this study was to determine the subsurface structure of Mount Banda Api. This research was conducted by analyzing the gravity method by processing topographic and gravity data carried out by PSDMBP in 2016 which resulted in the Complete Bouger anomaly. The complete Bouger anomaly range is 130-200 mGal with low values located on the Banda Api volcano and high anomalies on Neira Island and Lonthoir Island. Then performed 2D spectral analysis to determine the estimated depth of about 2.5 Km and a window width of 13 which is used for anomaly seperation method moving average . Separation of anomalies is done by two methods, which is moving average and second-order polynomial. The anomaly seperation results are compared to obtain optimal results. The residual anomaly using the moving average method and the second-order polynomial shows a low anomaly at the peak of Mount Banda Api which is indicated by the presence of molten magma at the bottom. In the forward modeling 2,5 D of geophysics, which the input data is residual moving average anomaly with anomaly range of -40 – 8 mGal and topographic data with background density of 2.63 g/cc. Through 2.5D modeling, the low anomaly in the study is estimated as a response to the presence of molten magma at the bottom of Mount Banda Api, while the high anomaly is a response from rocks that have an old age. In the geological model, five faults were obtained. Two of them are faults that were formed due to the collapse of the Ancient Neira Volcano, resulting in the structure of the Neira Caldera. There are two magma pathways, namely, the Mount Banda Api magma path and the Ancient Neira Volcano Magma path, each of which is blocked by frozen magma.